1994
DOI: 10.1039/an9941902581
|View full text |Cite
|
Sign up to set email alerts
|

Endogenic nortestosterone in cattle?

Abstract: When residues of nortestosterone (NT) were found in the urine of cattle, racehorses or bodybuilders, exogenic administration was thought to be proven. In previous literature, no records were found of the endogenic presence of this molecule. In the horse-racing world, Houghton and Courthot found that NT is normally present in the urine of the stallion. Belgian and Dutch researchers found that NT is also present in the urine and edible parts of the intact boar. Vandenbroeck et al. (1991) suggested the endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 2 publications
4
40
1
Order By: Relevance
“…6,7 There is added impetus to establish the nature of major metabolites in target samples given the recent EU Directive 1 requiring increased on-farm sampling, and reports that there may be endogenous sources of 19NT. [7][8][9][10][11] In this study, radiotracer, chromatographic and mass spectrometric procedures were used to investigate the disposition and biotransformation of 19NT laurate (19NTL) in cattle, with the aim of establishing appropriate target residues and tissues for surveillance of 19NT use. solved in dichloromethane (80 ml).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 There is added impetus to establish the nature of major metabolites in target samples given the recent EU Directive 1 requiring increased on-farm sampling, and reports that there may be endogenous sources of 19NT. [7][8][9][10][11] In this study, radiotracer, chromatographic and mass spectrometric procedures were used to investigate the disposition and biotransformation of 19NT laurate (19NTL) in cattle, with the aim of establishing appropriate target residues and tissues for surveillance of 19NT use. solved in dichloromethane (80 ml).…”
Section: Introductionmentioning
confidence: 99%
“…The androgen boldenone can be synthesized de novo in cattle feces by microbial activity [19][20][21]. Nandrolone has been detected in the urine of pregnant cows in their last trimester of pregnancy [22,23] and their calves for up to 7 d after birth [23]. The synthetic progestogens melengestrol and melengestrol acetate were included because they are supplemented into animal feed for growth promotion and synchronization of estrous [11].…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] In bovines, 17aN, ABA and NorE have also been detected as main metabolites in cows and calves. [14][15][16][17][18] 17bN, isomers of 3-hydroxyestran-17-one (NorA, NorE, NorEpiA) and isomers of estrane-3,17-diol (BAB and ABB) have been identified in miniature pigs after the administration of 17bN laurate. 19,20 In recent years, different authors have reported the endogenous production of 17bN or its metabolites in different species.…”
mentioning
confidence: 99%